The never-ending revival : Rounder Records and the Folk Alliance - Scully, Michael F. (Chicago : University of Illinois Press, 2008)
"In the late 1950s through the 1960s, the folk music revival pervaded the mainstream music industry, with artists such as Bob Dylan and Joan Baez singing historically or politically informed ballads based on musical forms from Appalachia and the South. In the twenty-first century, the revival continues, and it includes a variety of music derived from Cajun, African American, and Mexican traditions, among many others. Even though the mainstream music industry and media largely ignore the term "folk music," a strong allure based on nostalgia, the desire for community, and a sense of exclusiveness augments an enthusiastic following connected by word-of-mouth, numerous festivals, and the Internet. There are more folk festivals now than there were during the original boom of the 1960s, suggesting that music artists, agents, and record label representatives are striking a successful balance between tradition and profitability. Scully combines rich interviews of music executives and practicing folk musicians with valuable personal experience to reveal how this American subculture remains in a "never-ending revival" based on fluid definitions of folk and folk music."--Jacket.
"In recent years, there has been an upsurge of interest in "roots music" and "world music," popular forms that fuse contemporary sounds with traditional vernacular styles. In the 1950s and 1960s, the music industry characterized similar sounds simply as "folk music." Focusing on such music since the 1950s, The Never-Ending Revival: Rounder Records and the Folk Alliance analyzes the intrinsic contradictions of a commercialized folk culture. Both Rounder Records and the North American Folk Music and Dance Alliance have sought to make folk music widely available, while simultaneously respecting its defining traditions and unique community atmosphere. By tracing the histories of these organizations, Michael F. Scully examines the ongoing controversy surrounding the profitability of folk music. He explores the lively debates about the difficulty of making commercially accessible music, honoring tradition, and remaining artistically relevant, all without" selling out.""
Introduction. Where have all the folkies gone? -- Folklore, fakelore, and poplore : from the creation of the folk to the great boom and beyond -- From Club 47 to Union Grove : the birth of Rounder Records -- Surrealistic banjos and zydeco rhythms : Rounder's broad aesthetic -- Toward an authenticity of self : old-time music in the modern world -- Like politics in Chicago : the Folk Alliance strives for unity -- Consolidation blues : folk music in contemporary markets -- Conclusion. Gone to the Internet, everyone.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Rounder Records (Firm) -- History; North American Folk Music and Dance Alliance -- History; North American Folk Music and Dance Alliance; Rounder Records (Firm); Folk music -- United States -- History and criticism; Sound recording industry -- Social aspects -- United States; Musique folklorique -- États-Unis -- Histoire et critique; Enregistrements sonores -- Industrie -- Aspect social -- États-Unis.; MUSIC / General; Folk music; Sound recording industry -- Social aspects; United States; Folk music; Tonträgerindustrie; USA; musique folk -- Etats-Unis.; Criticism, interpretation, etc; History